Preventing school violence: an evaluation of an intervention program - Mendes, Carla Silva (Revista da Escola de Enfermagem da USP, 2011)
School violence (bullying), is currently considered a growing public health issue across the globe. It is essential to intervene in order to improve the quality of life of children/adolescents at school. Therefore, it should be a research priority to include the issue in the agenda of nurses. The objective of this study was to evaluate the results of an anti-violence program implemented with 307 secondary level students in a school in Lisbon. The evaluation before and after the program was performed using a questionnaire that was elaborated and validated for this study. We found that before the intervention, there was a high level of bullying (50% victims and 35% aggressors), and that the aggressions also included teachers (7%) and other school workers (9%). The program consisted of building awareness/preparation in teachers and parents and practicing social competencies among the students. After the intervention significant results were observed in the global reduction of school violence.